[ARTICLE RETRACTED] Ancestralities revealed: an analysis of Afrodiasporic Archeology in Brazil - Costa Vieira, Flávia Cristina; Souza Carmo, Sura (Brasiliana: Journal for Brazilian Studies, 2021)
This article analyses the expansion of the field of Afrodiasporic Archeology in Brazil. In its various approaches, these are works focused on sites, remains, collections, places, landscapes and human remnants related to the African diaspora. The objective of the article is to take stock of the scholarship already published, seeking to demonstrate the significant increase in the number of works published on the topic. To this end, the article makes a brief analysis of the expansion of Archeology in Brazil from the end of the nineteenth century, contextualizing the process of consolidation of the scientific field. Although the qualitative analysis was based on a large number of publications on the subject, it was not intended to be a comprehensive survey. The article also argues that the growth of the field has also been associated with external factors, such as actions of the black movement and valorization of Afro-Diasporic heritage by IPHAN and UNESCO, reflecting a broader understanding of heritage and the importance of research oriented based on diverse epistemologies.